THE ACCOMMODATION OF GOALS, BELIEFS AND VALUES OF CONSTRUCTIVISM IN THE TECHNOLOGY-BASE ENGLISH LEARNING AND TEACHING - Rosalina Ritonga, Theresia; Sumarni, Sri (UIN Sumatera Utara, 2024)
The advancement of technology has significantly transformed the way we study and teach. By effectively utilizing various learning theories, technology can be applied and integrated in a more proficient manner. The relationship between constructivism and technology is closely intertwined, as the application of one field enhances the progress of the other. According to constructivism, technology encompasses the surroundings and designs that actively engage learners, and learning takes place within these specific contexts. In recent times, there have been endeavors to incorporate technology into the classroom based on the principles of constructivist theory. This research paper aims to explore several key topics, including the definition of constructivism, successful integration of technology in the classroom, factors influencing teachers' use of technology, the role of technology in a constructivist learning environment, and how teachers apply learning theories to facilitate more efficient learning experiences.